2009
DOI: 10.1007/s10238-009-0062-0
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of serum soluble transferrin receptor in alcoholics

Abstract: The consumption of large amounts of alcohol disturbs body iron metabolism and leads to increase of body iron stores and may cause various hematologic changes. Both, iron overload and iron depletion could have effect on the metabolic, transit and storage pools. These pools and its indicators were evaluated previously in abusers, but there is no information concerning the serum soluble transferrin receptor (sTfR) as a new marker of transit compartment. Therefore, the aim of this study was to assess the sTfR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…May remain similar to corresponding controls (Unknown function; elevated in the serum in iron deficiency anemia) [20] • Reference range: 2.2-5.0 mg/L; In controls: 2.65 (1.9-3.7) mg/L (n = 30; social drinkers consumed less than 30 g/day (210 g/week)) [20] • In non-dependents on alcohol (social drinkers): 2.9 mg/L (n = 115; alcohol non-dependents with a negative AUDIT score of ≤ 6/8 and negative diagnosis of alcohol dependence, as defined by ICD-10 and DSM-IV) [ • Reference range: 11.17-17.0 g/dL; [70] • Range in controls: 1.4 ± 0.1 g/dL (n = 20; alcohol consumption less than 20 g/day in women and 40 g/day in men) [25] • In non-dependents on alcohol (social drinkers): 14.2 g/dL (n = 115; alcohol non-dependents with a negative AUDIT score of ≤ 6/8 and negative diagnosis of alcohol dependence, as defined by ICD-10 and DSM-IV) [68] • 12-18 g/dL in 82.5% of patients; 13.35 g/dL (2.16) (total number of patients = 103); consumption of at least 16 g/day or 2 units (drinks)/day) [47] • 1.4 ± 0.2 g/dL (n = 25; ALD active drinkers without cirrhosis, average daily alcohol intake of 154 g) [25] • 14.6 g/dL (n = 101; alcohol dependent patients with a positive AUDIT score of > 6/8 and positive diagnosis for alcohol dependence, as defined by ICD-10 and DSM-IV) [68] May be lower than corresponding controls or at lower end of reference range…”
Section: Iron-related Proteins and Parameters In Serumsupporting
confidence: 64%
See 4 more Smart Citations
“…May remain similar to corresponding controls (Unknown function; elevated in the serum in iron deficiency anemia) [20] • Reference range: 2.2-5.0 mg/L; In controls: 2.65 (1.9-3.7) mg/L (n = 30; social drinkers consumed less than 30 g/day (210 g/week)) [20] • In non-dependents on alcohol (social drinkers): 2.9 mg/L (n = 115; alcohol non-dependents with a negative AUDIT score of ≤ 6/8 and negative diagnosis of alcohol dependence, as defined by ICD-10 and DSM-IV) [ • Reference range: 11.17-17.0 g/dL; [70] • Range in controls: 1.4 ± 0.1 g/dL (n = 20; alcohol consumption less than 20 g/day in women and 40 g/day in men) [25] • In non-dependents on alcohol (social drinkers): 14.2 g/dL (n = 115; alcohol non-dependents with a negative AUDIT score of ≤ 6/8 and negative diagnosis of alcohol dependence, as defined by ICD-10 and DSM-IV) [68] • 12-18 g/dL in 82.5% of patients; 13.35 g/dL (2.16) (total number of patients = 103); consumption of at least 16 g/day or 2 units (drinks)/day) [47] • 1.4 ± 0.2 g/dL (n = 25; ALD active drinkers without cirrhosis, average daily alcohol intake of 154 g) [25] • 14.6 g/dL (n = 101; alcohol dependent patients with a positive AUDIT score of > 6/8 and positive diagnosis for alcohol dependence, as defined by ICD-10 and DSM-IV) [68] May be lower than corresponding controls or at lower end of reference range…”
Section: Iron-related Proteins and Parameters In Serumsupporting
confidence: 64%
“…Some ALD patients have shown serum iron levels similar to controls [20][21][22]. Moreover, a study showed similar levels of serum iron in patients with ALD cirrhosis, alcoholic hepatitis, and healthy volunteers that did not demonstrate any acute or chronic health conditions and consumed alcohol within the recommended guidelines [21].…”
Section: What Is the Status Of Serum Iron In Alcohol Consumers/ald Pa...mentioning
confidence: 93%
See 3 more Smart Citations